2010
DOI: 10.1021/bm1006272
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Cellular Internalization of Multifunctional Star Polymers Prepared by Atom Transfer Radical Polymerization

Abstract: Poly(ethylene glycol) (PEG) star polymers containing GRGDS (Gly-Arg-Gly-Asp-Ser) peptide sequences on the star periphery were synthesized by atom transfer radical polymerization (ATRP) of poly(ethylene glycol) methyl ether methacrylate (PEGMA), GRGDS modified poly(ethylene glycol) acrylate (GRGDS-PEG-Acryl), fluorescein o-methacrylate (FMA), and ethylene glycol dimethacrylate (EGDMA) via an "arm-first" method. Star polymers were approximately 20 nm in diameter, as measured by dynamic light scattering and atomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 63 publications
1
45
0
Order By: Relevance
“…4a). Flow cytometry experiments showed that peptide functionalization increased cellular uptake in vitro [166,175]. FITC-Dx-loaded nanogels were also able to effectively internalize into a spheroidal co-culture of human umbilical vascular endothelial cells (HUVECs) and human mesenchymal stem cells (hMSCs), which validated cellular endocytosis into a more complex system (Fig.…”
Section: Drug Delivery Systemsmentioning
confidence: 93%
“…4a). Flow cytometry experiments showed that peptide functionalization increased cellular uptake in vitro [166,175]. FITC-Dx-loaded nanogels were also able to effectively internalize into a spheroidal co-culture of human umbilical vascular endothelial cells (HUVECs) and human mesenchymal stem cells (hMSCs), which validated cellular endocytosis into a more complex system (Fig.…”
Section: Drug Delivery Systemsmentioning
confidence: 93%
“…The unique architecture of CCS polymers has enabled their applications in a wide array of areas, including drug delivery, imaging, catalysis, sensing, film formation, and self‐assembly . While the potential of CCS polymers in these applications has been well appreciated, their use as interfacial stabilizers has been much less studied.…”
Section: Applications Of Ccs Polymers As Interfacial Stabilizersmentioning
confidence: 99%
“…Great effort has been devoted to the synthesis of nanoparticlebased drug delivery systems for cancer therapy (1)(2)(3). Many basic parameters of ideal systems have been defined (4)(5)(6), and a myriad of materials have been reported (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21); many are nearing clinical use (22)(23)(24)(25)(26)(27). There remains room for improvement, particularly in the realm of efficient drug carrier synthesis.…”
Section: Introductionmentioning
confidence: 99%